Beyond Compliance: Operationalizing Internal Quality Assurance Systems for Enhanced Teacher and Principal Performance - Johan Andriesgo; Abu Anwar; Ahmad Jailani; Zohaib Hassan Sain (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the relationship between the implementation of the Internal Quality Assurance System (SPMI), teacher performance, and madrasah principal leadership. This study used a descriptive correlational design with a quantitative approach involving 100 teachers as respondents. Data were collected through a structured questionnaire consisting of 17 valid items to measure the implementation of SPMI, teacher performance, and madrasah principal leadership. The research instrument has a very high level of reliability with a Cronbach's Alpha value of 0.988. Data were analyzed using descriptive statistics and Spearman's rho correlation. The results showed that the implementation of SPMI was in the very good category (M = 4.35), followed by teacher performance (M = 4.56) and madrasah principal leadership (M = 4.65). The implementation of SPMI has a positive and significant relationship with teacher performance (r = 0.624; p < 0.001) and madrasah principal leadership (r = 0.530; p < 0.001). This study demonstrates that effective implementation of the PPEPP cycle can strengthen a culture of quality, enhance teacher professionalism, and support effective educational leadership. These findings provide an empirical contribution to the development of educational quality management through the integration of quality assurance practices, teacher performance, and madrasah leadership.